2014
DOI: 10.1590/1678-7576
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candida species isolated from cows suffering mastitis in four Brazilian states

Abstract: Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…In this study, Candida species of yeasts were isolated in the 23.44% (60/256) of all samples analyzed. This rate is a marginally higher than the rates reported in Turkey were 12.7% [ 9 ], 17.7% [ 10 ]; the rates reported in Brazil were 17.3% [ 4 ], 12.8% [ 11 ]; and the rate reported in Slovenia was 7.5% [ 12 ]. C. krusei was the predominant species isolated in this study, which was 23.33% (14/60) of the Candida isolates from those with clinical mastitis.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In this study, Candida species of yeasts were isolated in the 23.44% (60/256) of all samples analyzed. This rate is a marginally higher than the rates reported in Turkey were 12.7% [ 9 ], 17.7% [ 10 ]; the rates reported in Brazil were 17.3% [ 4 ], 12.8% [ 11 ]; and the rate reported in Slovenia was 7.5% [ 12 ]. C. krusei was the predominant species isolated in this study, which was 23.33% (14/60) of the Candida isolates from those with clinical mastitis.…”
Section: Discussionmentioning
confidence: 72%
“…However, there is some discrepancy among rates that were also reported by others. Pengov et al reported a 34% [ 12 ], De&Marin et al reported a 44.5% [ 4 ], and Sartori et al reported a 34.6% [ 11 ] of C. krusei isolates from cows with mastitis. Their data reported a higher frequency of C. krusei infection than findings in this report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This organism may be an aetiological agent in cow mastitis (Dworecka-Kaszak et al 2012;Sartori et al 2014). The size and shape of these yeasts are similar to somatic cells and in order to distinguish them from SC we inoculated Candida albicans into distilled water and stained them with EtBr according to Method B.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial opposition to beta-lactam mechanisms comprises of generation protein which is a low-affinity penicillin-binding as well as secretion of beta-lactamases (Ksouri et al 2015). Antibacterial agents from crops are substantial sources of new antibiotics compounds and efflux pump inhibitors which target bacterial virulence or can be adopted in mixture with other prevailing drugs (Sartori et al 2014). The plants generate a significant constituent of ethno-veterinary remedy that is implemented in the therapy of diverse disorders such as bovine mastitis (Sağlam et al 2017).…”
Section: Introductionmentioning
confidence: 99%